2011
DOI: 10.1099/mic.0.044537-0
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and genetic variation among Fe(II)-oxidizing acidithiobacilli supports the view that these comprise multiple species with different ferrous iron oxidation pathways

Abstract: Autotrophic acidophilic iron-and sulfur-oxidizing bacteria of the genus Acidithiobacillus constitute a heterogeneous taxon encompassing a high degree of diversity at the phylogenetic and genetic levels, though currently only two species are recognized (Acidithiobacillus ferrooxidans and Acidithiobacillus ferrivorans). One of the major functional disparities concerns the biochemical mechanisms of iron and sulfur oxidation, with discrepancies reported in the literature concerning the genes and proteins involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(98 citation statements)
references
References 65 publications
7
90
1
Order By: Relevance
“…This 336 genome contains two identical copies of the 16S rRNA gene, but these show only 337 97.6% sequence identity to that of the type strain. This is comparable to the 338 15 difference between the distinct species, T. denitrificans and T. thioparus (Table 1) Acidithiobacillus ferrooxidans (Amouric et al 2011;Harrison 1982;Karavaiko et al 360 2003;Kelly and Harrison 1989;Waltenbury et al 2005). Our study has confirmed the species affiliations of a number of phenotypically similar 365 strains of Thiobacillus thioparus, but has reassigned two strains originally defined 366 solely by their physiological properties as T. thioparus to two alternative genera.…”
Section: Materials and Methods 150 151supporting
confidence: 59%
“…This 336 genome contains two identical copies of the 16S rRNA gene, but these show only 337 97.6% sequence identity to that of the type strain. This is comparable to the 338 15 difference between the distinct species, T. denitrificans and T. thioparus (Table 1) Acidithiobacillus ferrooxidans (Amouric et al 2011;Harrison 1982;Karavaiko et al 360 2003;Kelly and Harrison 1989;Waltenbury et al 2005). Our study has confirmed the species affiliations of a number of phenotypically similar 365 strains of Thiobacillus thioparus, but has reassigned two strains originally defined 366 solely by their physiological properties as T. thioparus to two alternative genera.…”
Section: Materials and Methods 150 151supporting
confidence: 59%
“…A multilocus sequence analysis (MLSA) of 21 strains of iron-oxidizing acidithiobacilli using five different markers defined four monophyletic subgroups, which correspond to different species (Amouric et al 2011). Group I includes A. ferrooxidans T .…”
Section: Introductionmentioning
confidence: 99%
“…Neither the Zetaproteobacteria SAGs nor isolates contain homologs to well-characterized genes involved in iron oxidation identified in other microorganisms including iro (Amouric et al, 2011), rus (Cox and Boxer, 1978), mtoAB (Shi et al, 2012), pioABC , foxEYZ (Croal et al, 2007) and cyt579 (Singer et al, 2008). Previous studies have suggested that the Zetaproteobacteria may use a molybdopterin oxidoreductase and alternative respiratory complex III mechanism to carry out iron oxidation (Singer et al, 2011).…”
Section: Potential For Iron Oxidationmentioning
confidence: 99%